Sequence, expression, and localization of the immunity protein for colicin M. - Olschläger, T (1987)
Escherichia coli strains carrying the cmi locus on plasmids are immune against colicin M, which primarily inhibits murein biosynthesis, followed by lysis of cells. The nucleotide sequence of the cmi region was determined. It contains an open reading frame for a polypeptide with a molecular weight of 19,227. However, the major protein band observed on polyacrylamide gels after transcription and translation in an in vitro system or in minicells had an apparent molecular weight between 15,000 and 16,000. The nucleotide sequence contained internal ATG codons, two of which could serve for the synthesis of polypeptides with molecular weights of 15,349 and 15,996, respectively. A subclone with a DNA fragment that encoded these two shorter polypeptides exhibited full immunity. The colicin M immunity protein was found in the cytoplasmic membrane. The colicin M activity and immunity genes were transcribed in opposite directions. Both properties are typical of the channel-forming colicins and are in contrast to the colicins with endonuclease activities. However, colicin M does not form channels and exhibits no structural similarity to channel-forming colicins.